Study The Effect of Doping Zinc Oxide Thin Films With (0.5 wt. %) Carbon Nanotubes by Vacuum Evaporation - ahmed mansoor; Walla Mohammd (Tikrit Journal of Pure Science, 2024)
The study included the production of nano-thin films made of zinc oxide doped with carbon nanotubes (ZnO:CNTs) at a doping ratio of 0.5 wt%. The materials are applied onto glass substrates using the vacuum evaporation process. The structural characteristics of the thin films of undiluted and doped ZnO were assessed using X-ray diffraction (XRD). Additionally, the surface properties of the films were examined using scanning electron microscopy (SEM) and atomic force microscopy (AFM). The optical characteristics of the thin films were analyzed and described using UV-Vis spectroscopy. The ZnO thin films exhibited crystalline formations. The thin films exhibited significant orientations along the (100), (002), and (101) crystallographic planes, indicating their hexagonal phase structures. The crystal size of ZnO thin films exhibited a range of 30.87 nm to 19.96 nm after the process of doping. The study findings demonstrate that the addition of carbon nanotubes leads to an increase in the absorption ratio. Zinc-doped carbon nanotube thin films has features that make them suitable for many applications, such as gas detectors and UV detectors.